Consuelo Ruiz Montero, La novela griega, Madrid, Editorial Síntesis, 2006, 237 págs. ISBN: 978-84-9756-450-2 (Minerva, 2019)
Review: Consuelo Ruiz Montero, La novela griega, Madrid, Editorial Síntesis, 2006, 237 págs. ISBN: 978-84-9756-450-2